2019
DOI: 10.1021/acs.jpca.9b03366
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Selective-Sensing Mechanism of Al3+ Cation by a Chemical Sensor Based on Schiff Base: A Theoretical Approach

Abstract: A methodology that allows us to explain the experimental behavior of a turn-on luminescent chemosensor is proposed and verified in 1-[(1H-1,2,4-triazole-3-ylimino)-methyl]-naphthalene-2-ol] (L1), selective to Al 3+ cations. This sensor increases its emission when interacting with ions upon excitation at 442 nm, which is denoted as the chelation-enhanced fluorescence effect. Photoinduced electron transfer is responsible for the fluorescence quenching in L1 at 335 nm, in Ni 2+ /L1 at 385 nm, and in Zn 2+ / L1 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…A precise description, both of the S 0 state and of the S 1 state, in terms of energy and structure, allowed us to explain in detail the turn‐on fluorescent mechanism of the two chemosensor luminescents based on Schiff basis selective to metal ions. [ 60,61 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise description, both of the S 0 state and of the S 1 state, in terms of energy and structure, allowed us to explain in detail the turn‐on fluorescent mechanism of the two chemosensor luminescents based on Schiff basis selective to metal ions. [ 60,61 ]…”
Section: Resultsmentioning
confidence: 99%
“…A precise description, both of the S 0 state and of the S 1 state, in terms of energy and structure, allowed us to explain in detail the turn-on fluorescent mechanism of the two chemosensor luminescents based on Schiff basis selective to metal ions. [60,61] Considering the importance of knowing that the emissive state of chemosensor is optimized, the S 1 state of the Zn-MOF is used to understand the origin of fluorescence in this system. Thus, the optimized geometry of the S 1 state was taken as input data to calculate the electronic transitions that constitute the emission spectrum of Zn-MOF by means of TD-DFT methods.…”
Section: Fluorescence Quenching Pathwaymentioning
confidence: 99%
“…The added metal ions may affect the LMET process in 1 due to their perturbation to the electronic structure and excited state of the Schiff base ligand, resulting in so‐called chelation enhancement of the quenching emission (CHEQ) effect. [ 34 ] For example, d‐block metal ions such as Co 2+ , Cu 2+ , Fe 3+ , Ni 2+ and Cr 3+ may quench the lanthanide luminescence through f→d energy transfers. [ 35,36 ] The luminescence response of 1 to the addition of Cd 2+ ion has been further studied through UV‐vis titration.…”
Section: Resultsmentioning
confidence: 99%
“…For 1 + Hg 2+ / 1· H 2 O + Hg 2+ complex, the HOMO is predominantly localized on the Hg 2+ central metal ion and the coordinated N, O atoms, while the LUMO is essentially spread over the whole molecule (Tables S1–S3, Supporting Information), which induced charge transfer from the Hg 2+ center to the excited moiety thus providing a fluorescence quenching result. [ 9c,34 ] Nevertheless, the calculations revealed that compound 1· H 2 O + Hg 2+ was not stable since the boric acid ester ring would break when optimized the structure at PBE0/B3LYP method.…”
Section: Resultsmentioning
confidence: 99%